Impacts of forest fire on people living in suburban Kathmandu in the buffer zone of Shivapuri Nagarjun National Park (Samriddhi Journal of Development Studies, 2022)
The research study mainly intends to gauge the impact of forest fire in the buffer zone community of Shivapuri Nagarjun National Park, mainly in the area of Chapali Bhadrakali (ward number 2) adjacent to the sprawling Kathmandu metropolitan city. The study reflects the frequent occurrence of forest fire events happening in the area and its effects, both physical and psychological, on the local communities in the buffer zone. The locals have their work cut out due to the repetition of the incident every year leaving them no alternative than to ready themselves to face the challenges. Thus, the research paper includes both the threats caused by forest fires to people’s livelihoods as well as the local’s perception regarding the fire incidents. Ergo, this study analyzes the impact status of the buffer zone community of Chapali Bhadrakali with regard to seasonal forest fire events.